Valeriana officinalis (Valerian) – review - Kokitko, V. I.; Odyntsova, V. M.; Кокітко, Валерія Ігорівна; Одинцова, Віра Миколаївна (Запорізький державний медико-фармацевтичний університет, 2024)
The aim of the work was searching, systematizing, and generalizing information from the specialized literature on the chemical composition, biological activity and therapeutic use of Valeriana officinalis. Valeriana officinalis has sedative, mild analgesic, hypnotic, antispasmodic, carminative, and hypotensive effects. Historically, it was used for hysterical conditions, hyperexcitability, insomnia, hypochondria, migraine, spasms, intestinal colic, rheumatic pains, dysmenorrhea, and especially for conditions accompanied by nervous excitability. The main classes of biological substances identified in Valeriana officinalis are valepotriates, iridolactones, alkaloids, phenolic acids, sesquiterpenes, flavonoids, terpene coumarins, lignans, terpene and flavonol glycosides. It has not yet been established which components of Valeriana officinalis are responsible for its pharmacological effects. Current opinion is that the overall effect of valerian is due to several different groups of components and their different mechanisms of action. Therefore, the activity of different preparations of valerian will depend on their content and concentration of several types of components. Мета роботи – пошук, систематизація та узагальнення відомостей фахової літератури щодо хімічного складу, біологічної активності та терапевтичного застосування Valeriana officinalis. Valeriana officinalis має заспокійливу, легку болезаспокійливу, снодійну, спазмолітичну, вітрогонну та гіпотензивну дії. Історично її використовували при істеричних станах, підвищеній збудливості, безсонні, іпохондрії, мігрені, спазмах, кишкових кольках, ревматичних болях, дисменореї, а особливо при станах, що супроводжуються нервовою збудливістю. Основними класами біологічних речовин, які ідентифіковано в Valeriana officinalis, є валепотріати, іридолактони, алкалоїди, фенольні кислоти, сесквітерпени, флавоноїди, терпенові кумарини, лігнани, терпенові та флавонолові глікозиди. Досі не встановлено, які саме компоненти Valeriana officinalis спричиняють її фармакологічні ефекти. Нині вважають, що загальний ефект валеріани зумовлений кількома різними групами компонентів з їхніми різними механізмами дії. Отже, активність різних препаратів валеріани залежатиме від складу та концентрації компонентів кількох типів.
Valeriana officinalis (Valerian) – огляд
Kokitko V. I. - ORCID ID: 0000-0001-9231-7627; Odyntsova V. M. - ORCID ID: 0000-0002-7883-8917.
Keywords: Valeriana officinalis L.; Valerianaceae; chemical composition; therapeutic significance; biological activity; хімічний склад; терапевтичне значення; біологічна активність